Aspects of Impurities Control at Caraiba Metais' Electrorefinery - José Luiz Rodrigues Bravo (The Minerals, Metals and Materials Society, 1997)
The production of electrolytic copper with assured quality corresponding to international standards, in a conventional electrorefkery of a custom smelter, is a hard and cautious task, if no advanced technologies for selective control of electrolyte impurities are available. The improper control of the amount of As , Sb and Bi in the anode that enter the tankhouse , attributable either to a bad schedule of concentrate input or to the unavailability of clean concentrates in the international market , as well as the lack of means to maintain the suitable level of these elements in the electrolyte together with other operational circumstances, can result in off-grade copper, as well as affect the starting sheet chemically and physically. This paper presents in a practical way the relationship between the operational conditions and the cathode and starting sheet quality produced at CMSA, covering the period of the last five years of operation, discusses the technologies available in the market for antimony and bismuth removal and compare the results of testwork, achieved in the laboratories of CMSA, using two resins not associated with patented technologies.